2013
DOI: 10.1002/ajim.22197
|View full text |Cite
|
Sign up to set email alerts
|

The role of ergonomic and psychosocial workplace factors in the reporting of back injuries among U.S. home health aides

Abstract: Background Due to the aging population and a shift to patient home care, Home Health Aides (HHAs) are a fast-growing occupation. Since little is known about workplace risk factors for back injuries among HHAs, we examined the role of ergonomic and psychosocial factors in injury reporting among HHAs. Methods We used the 2007 U.S. National Home Health Aide Survey data (weighted n=160,720) to predict the risk of back injuries by use of/need for ergonomic equipment and supervisor support with logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This study found that requests for tasks outside the job are a commonly‐encountered issue for aides, and are ranked among the top job hazards for which they would like intervention. Both quantitative and qualitative analyses suggest that extra requests may be associated with OSH hazards and negative outcomes that have been previously identified as concerns in HC, including psychosocial stress, conflict or abusive client behaviors, and injury and musculoskeletal pain . The types of tasks requested, as identified in the qualitative analysis, reflect potential pathways to the negative outcomes found in the quantitative analysis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This study found that requests for tasks outside the job are a commonly‐encountered issue for aides, and are ranked among the top job hazards for which they would like intervention. Both quantitative and qualitative analyses suggest that extra requests may be associated with OSH hazards and negative outcomes that have been previously identified as concerns in HC, including psychosocial stress, conflict or abusive client behaviors, and injury and musculoskeletal pain . The types of tasks requested, as identified in the qualitative analysis, reflect potential pathways to the negative outcomes found in the quantitative analysis.…”
Section: Discussionmentioning
confidence: 79%
“…Both quantitative and qualitative analyses suggest that extra requests may be associated with OSH hazards and negative outcomes that have been previously identified as concerns in HC, including psychosocial stress, 15,21,22 conflict or abusive client behaviors, 9,[23][24][25][26][27] and injury and musculoskeletal pain. 9,28,29 The types of tasks requested, as identified in the qualitative analysis, reflect potential pathways to the negative outcomes found in the quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of ergonomic aids, as reported by Arlinghaus et al . (), as well as lack of colleague support in the home‐care setting may further increase these risks. Similar to the HHN characteristics, HHAs in the present study were mostly obese and over the age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Arlinghaus et al . () report data supporting an increase in back injuries for HHAs who reported insufficient ergonomic aids. Overall, the physical burden appears to be high for home health‐care workers but relatively little is known about the frequency of ergonomic concerns.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation